2020
DOI: 10.1007/jhep09(2020)166
|View full text |Cite
|
Sign up to set email alerts
|

Geometries with mismatched branes

Abstract: We study Randall-Sundrum two brane setups with mismatched brane tensions. For the vacuum solutions, boundary conditions demand that the induced metric on each of the branes is either de Sitter, Anti-de Sitter, or Minkowski. For incompatible boundary conditions, the bulk metric is necessarily time-dependent. This introduces a new class of time-dependent solutions with the potential to address cosmological issues and provide alternatives to conventional inflationary (or contracting) scenarios. We take a first st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…We will further see that this is precisely the dynamics in the bulk that saves us from the undesirable time dependence, which was a concern in some recent papers [11,12]. In the context of a 2-brane model, [12] showed that the effective G 4 depends on the time dependent relative position (parametrized by the radion) of a cutoff brane. They did find that a change of frame to Einstein frame actually makes G 4 time independent, but this was of no help since any matter dependent on the radion would have the undesired time dependence.…”
Section: Jhep03(2021)250mentioning
confidence: 79%
See 4 more Smart Citations
“…We will further see that this is precisely the dynamics in the bulk that saves us from the undesirable time dependence, which was a concern in some recent papers [11,12]. In the context of a 2-brane model, [12] showed that the effective G 4 depends on the time dependent relative position (parametrized by the radion) of a cutoff brane. They did find that a change of frame to Einstein frame actually makes G 4 time independent, but this was of no help since any matter dependent on the radion would have the undesired time dependence.…”
Section: Jhep03(2021)250mentioning
confidence: 79%
“…We perform a JHEP03(2021)250 worldsheet analysis to understand their role in producing four dimensional gravity on the shellworld, and comment on the analogy between mass renormalization and holographic renormalization. In section 4, we comment on the time dependence that was pointed out in recent results of [11,12] and how it is evaded in the shellworld construction. Finally, we conclude with a summary in section 5.…”
Section: Jhep03(2021)250mentioning
confidence: 98%
See 3 more Smart Citations